Research progress on gels-based nanocomposites in the diagnostics and therapy of prostate diseases. (March 2023) - Zhong, R.; Chu, R.; Zhu, J.; Ling, J.; Zhang, L.; Zhou, Y.; Yin, M.; Hao, Z.; Liang, C.; Cao, S.; Xu, T.; Ye, S.; et al.
Abstract: Prostate diseases are common and frequently-occurring diseases in males. Nanomedicine is the interdisciplinary integration of medicine and materials science that brings great opportunities to the biomedical field by designing and manufacturing biomaterials to satisfy clinical practice needs. Gels are a very promising material with a wide range of applications in the biomedical field. There are numerous research reports on the important role of gels in drug delivery and release, anti-inflammation and anti-infection, promotion of tissue regeneration, and wound healing. In this review, we overview prostate diseases and the classification of gels and focus on the current research on gels-based nanocomposites in the diagnostics and therapy of prostate diseases. Moreover, the shortcomings of gels-based nanocomposites for prostate diseases are pointed out, and we look forward to a broader prospect of the clinical application of gels-based nanocomposites in prostate diseases in the future, which provides a new strategy for diagnostics and therapy of prostate diseases. Graphical abstract: We focus on the current research progress on gels-based nanocomposites in the diagnostics and therapy of prostate diseases. Moreover, we look forward to a broader prospect of the clinical application of gels-based nanocomposites in prostate diseases. Image 1